Commodity market volatility in the presence of U.S. and Chinese macroeconomic news - Smales, Lee (2017)
© 2017 Elsevier B.V. Utilising a comprehensive sample of U.S. and Chinese macroeconomic news announcements, we determine that volatility in commodity prices is significantly impacted by news that conveys information regarding prospective demand for commodities. This includes news regarding U.S. employment and economic output together with the purchasing intentions of Chinese manufacturers. Commodity price volatility is also closely related to the cost of credit. Much of this effect appears to be driven by volatility in the Energy markets. During the 2007-09 crisis, commodity markets appear to pay more attention to forward-looking macroeconomic news, such as PMI surveys.